Designing the Business Scheme Model of Direct Investment of Indonesian Hajj Funds to The Saudi Food Industry - Majid, Rifaldi (Department of Islamic Economics, IPB University, 2025)
Diversification of investment in hajj funds is also needed in the real sector to optimize the portfolio and sustainable development of hajj finance. This study analyzes the potential for direct investment in the supply of raw materials to meet the needs of catering and processed food by the Indonesian Hajj Fund Management Agency in Saudi Arabia’s food industry. This research utilized a qualitative approach and used data and regulations from authorities and regulators in Indonesia and Saudi Arabia. All available data is used to design direct investment models using contracts complying with ethical and fair investment principles. The results depicted two alternative investment schemes: executing a joint venture or establishing a subsidiary. Murabaha and parallel salam can carry out the business contract schemes. Using the murabaha scheme, the risk of fluctuations in exchange rates and commodities can be controlled by setting the margins. Meanwhile, salam contracts are explicitly made for orders obtained from local suppliers to avoid the risk of exchange rate fluctuations. This research is limited to the condition of hajj financial management in Indonesia and Saudi Arabia. However, this research is expected to improve the literature on the management of hajj finance and provide an alternative way for innovative and sustainable direct investment performed by the Indonesian Hajj Financial Management Agency.